Shontengan : Tradisi Sesajen dalam Pesta Pernikahan Menurut Kacamata Hukum Islam (Studi Sumur Mortandek di Desa Pragaan Laok Sumenep) - Usmany, Nuri Wahda Salsabila; Hamdani, Hamdani (Journal of Linguistics and Social Studies, 2025)
Shontengan is a tradition that still continues among the Pragaan Laok community, where the belief in the Mortandek well guard is still inherent and attracts people to continue making offerings every time they hold a wedding. The aim of this research is to draw out and determine the laws of existing offering practices through the lens of Islamic law.This research uses a qualitative method with a descriptive approach, so that all forms of data obtained will be described in narrative form. The data source in this research uses primary data sources such as interview results, observation and documentation. while secondary sources are through literature related to legal studies on offerings. Then, this research was analyzed using data reduction, data presentation and drawing conclusions. The results of this research are: 1) people's thoughts on the practice of shontengan because they are afraid of the impacts that will be experienced after the wedding event, such as physical and non-physical disturbances. 2) Islamic law does not condone the practice of offering offerings because the action has the nuances of shirk (associating partners with God) and there is also the activity of wasting wealth (tabdzir).